PERAN PEMERINTAH DAERAH DALAM PENGELOLAAN DANA DESA UNTUK MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT - Kamila, Nazwa Feryal; Ryo Syahputra Wardana; Ramzi Fauzan; Wahjoe Pangestoeti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to critically analyze the role of local government in the management of Village Funds and its impact on improving the economic welfare of rural communities. The research employs a descriptive qualitative approach with case studies in selected villages representing diverse Village Fund implementation contexts. The findings reveal that local governments play a strategic role in planning (RPJMDes and RKPDes), providing technical assistance and training for village officials, and overseeing the monitoring and evaluation of fund utilization. Nevertheless, several challenges persist, such as limited human resource capacity at the village level, weak vertical-horizontal coordination, and low transparency and accountability in financial management. Despite these issues, Village Fund management has proven to yield positive effects on rural economic development, notably through improved infrastructure and productive economic empowerment. This is evident from the increased number of microenterprises, higher household income, and decreased rural unemployment. These findings are interpreted through the lens of good governance and participatory development theory. The study recommends stronger synergy between local and village governments in implementing participatory, transparent, and accountable financial governance to achieve sustainable community welfare.